Explicating the Sodium Storage Kinetics and Redox Mechanism of Highly Pseudocapacitive Binary Transition Metal Sulfide via Operando Techniques and Ab Initio Evaluation. Issue 7 (9th May 2019) - Lim, Yew Von; Huang, Shaozhuan; Hu, Junping; Kong, Dezhi; Wang, Ye; Xu, Tingting; Ang, Lay Kee; Yang, Hui Ying
Abstract: The economic advantage of sodium resources has triggered worldwide enthusiasm in sodium‐ion batteries (SIBs). As a new breed of transition metal sulfides, binary metal sulfides (BMS) have garnered increasing interests due to its pseudocapacitive capabilities but with limited reports to address its potentials. To address them, bimetallic nickel cobalt sulfide (NiCo2 S4, or NCS) embedded in graphene aerogel matrix (NCSGO) with excellent reaction kinetics and rate performance are studied by first‐principles methods and operando techniques to elucidate its sodiation kinetics and redox mechanism. The kinetic analysis on sodiation behavior reveals a major contribution of pseudocapacitance versus total capacity, providing fast reaction kinetics and highly reversible cycling. The sodiation dynamics are unraveled by first‐principles approach manifesting favorable Na + adsorption kinetics (<−2.1 eV) and extremely low diffusion barrier (0.28 eV), indicating the strong adsorption and diffusion capability for SIBs. The redox mechanism is studied and confirmed via operando techniques that NCS‐based electrodes are based on both a combination of intercalation and conversion reactions. Following the results of the joint experimental‐computational approach, the excellent BMS SIBs performance enabled by conversion‐based and fast pseudocapacitive sodiation kinetics provides a promising strategy for developing SIBs anodes with both high specific capacity and fast rate response. Abstract : Nickel cobalt sulfide in graphene matrix exhibits remarkable performance in sodium‐ion batteries, enabled by the fast Na‐ions kinetics, pseudocapacitive behavior, and conversion‐based redox mechanism, which are elucidated by a combined approach via operando and ab initio techniques.